Compliance to secondary prevention of smoking as a risk factor of recurrent myocardial infarction - Yakobson, Olena O.; Sitovskyi, Andrii M.; Ulianytska, Nataliia Ya.; Usova, Oksana V.; Yelisieva, Liudmila V. (My University, 2022)
Low level of awareness of the possibility of risk factors modifying for recurrent heart attack is associatedwith a low compliance to non-drug secondary prevention measures after MI such as smoking cessation (Fp=0,000) and alcohol reduction (χ2=35,29; p= 0,000).
Keywords: Compliance; myocardial infarction; smoking; cardiac rehabilitation; preventive medicine